Risk factors and outcomes of healthcare-associated infections in a Brazilian intensive care unit: A cross-sectional study - Andressa Maria de Sousa Moura; Álvaro Francisco Lopes de Sousa; Herica Emilia Félix de Carvalho; Maria Zélia de Araújo Madeira; Daniela Reis Joaquim de Freitas; Ana Carolina de Macedo Lima; Liliane Moretti Carneiro; Marilia Duarte Valim; Aires Garcia dos Santos Junior; Odinéa Maria Amorim Batista (Belitung Nursing Journal, 2026)
Background: Healthcare-associated infections (HAIs) in intensive care units (ICUs) are frequent and are associated with sepsis, antimicrobial resistance, and high mortality, reinforcing the need for early risk stratification at admission. Objective: To analyze risk factors and clinical outcomes associated with HAIs in ICU patients. Methods: This cross-sectional study was conducted in the ICU of a public hospital with 141 patients (182 HAI cases). Medical records covered ICU admissions from August 1, 2022, to August 31, 2024, and data collection occurred from November 2024 to February 2025. Data were extracted from medical records and the Hospital Infection Control Committee database. Risk factors were assessed at admission using the Rodríguez-Almeida-Cañon (RAC) Scale, which stratifies HAI risk using intrinsic and extrinsic factors and classifies patients as low, moderate, or high risk. Clinical outcomes monitored during hospitalization included hospital discharge, sepsis, septic shock, and death. Results: By RAC, 53.9% were moderate risk and 45.4% high risk; lower educational level was associated with higher risk (p = 0.016). Ventilator-associated pneumonia predominated (44.4%). Predominant pathogens were Pseudomonas (28.1%), Acinetobacter (19.1%), and Klebsiella (17.4%), with 34.3% showing carbapenem resistance. Sepsis occurred in 18.5% and septic shock in 30.2%; mortality was 62.9%. Compared with the reference group, odds of discharge were higher among patients aged 20–39 years (OR = 12.48; 95% CI: 4.89–102.90; p = 0.002) and 40–59 years (OR = 4.33; 95% CI: 3.89–35.78; p = 0.019). Conclusion: RAC screening revealed a high burden of predisposing factors at ICU admission, particularly among patients with lower educational levels, which was associated with worse outcomes. RAC-guided admission screening can support risk-proportional nursing surveillance and targeted prevention bundles, while institutional policies should reinforce microbiological surveillance and antimicrobial stewardship tailored to social vulnerability.